Pendapatan dari Gift dalam Live Streaming TikTok Perspektif Hadis Nabi: Analisis terhadap Harga Diri dan Rasa Malu - Miktahul Hasanah Siregar; Ardiansyah (Kartika: Jurnal Studi Keislaman, 2026)
The emergence of income through gifts on TikTok’s live streaming feature represents a new form of digital economic activity while raising ethical and religious concerns, particularly when income generation involves behaviors that may undermine self-esteem and erode a sense of shame. This study aims to analyze the practice of receiving income from gifts during TikTok live streaming from the perspective of Prophetic Hadith, particularly the principles of preserving personal dignity, avoiding begging, and maintaining a sense of shame in Islam. This qualitative study employs a hadith study approach. Data were collected through an examination of relevant hadiths from primary and secondary sources and analyzed thematically by relating their meanings to the phenomenon of TikTok live streaming. The findings indicate that receiving gifts can be considered permissible as long as the income is generated through lawful activities that do not involve self-exploitation, the display of awrah or personal disgrace, or behavior that compromises human dignity. Conversely, live streaming practices that deliberately exploit the body, dignity, or sense of shame to obtain gifts are inconsistent with the Prophetic values of preserving personal dignity (‘iffah) and modesty (haya’). These findings demonstrate that the permissibility of digital income is determined not only by the form of the transaction but also by the manner in which the income is obtained